Gereja Protestan di Timor Barat pada Masa Nederlandsch Zendeling Genootschap, 1820-1860: Suatu Kajian Mengenai Sejarah dan Bentuknya - Fransico de Ch. A. Jacob (Theologia in Loco, 2021)
This article aims to describe and analyze - as comprehensively and objectively as possible - how the history of the Protestant Church in West Timor, especially during the Nederlandsch Zendeling Genootschap (1820-1860), took place. The results obtained clearly show that the Protestant Church continues to experience growth despite various challenges. One notable thing is that the growth of the Protestant Church in West Timor during the NZG period was not only due to the works of European missionaries but also because of the work of local people, both men, women, adults, and children.